Value distribution of q-differences of meromorphic functions in several complex variables - Cao, T.-B.; Korhonen, R. J. (Analysis mathematica (Budapest), 2020)
In this paper, we study q -difference analogues of several central results in value distribution theory of several complex variables such as q -difference versions of the logarithmic derivative lemma, the second main theorem for hyperplanes and hypersurfaces, and a Picard type theorem. Moreover, the Tumura–Clunie theorem concerning partial q -difference polynomials is also obtained. Finally, we apply this theory to investigate the growth of meromorphic solutions of linear partial q -difference equations.